Proc. Indonesian Petrol. Assoc., 39th Ann. Conv.
DOI: 10.29118/ipa.0.15.g.016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unconformities and Subsequent Loading on Pore Pressure Profiles

Abstract: In summary, a combination of the 'Swarbrick Method' and an unconformity/loading model can be invoked to explain shale pressures in many basins. This geologically-based model for shale pore pressure has proved to be a successful forwardmodelling approach in well planning in these basins, where the only inputs required are ages of seismic markers and depth of the relevant unconformity to give maximum shale pressures, matching kicks taken in wells such as Montague-1 and Angel-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, this relatively simple model, describing porosity/effective stress evolution due to "primary" disequilibrium compaction, fails to capture the shale pressure in most of the study wells. For the purpose of this study, this relatively simplistic model can be further split into "primary" and "secondary" disequilibrium compaction where primary disequilibrium compaction relates to overpressure generated in rocks for the first time, whereas secondary disequilibrium compaction applies to rocks where overpressure has been previously generated, but, due to depositional hiatus or unconformity, the overpressure has dissipated, leading to low porosity/permeability rocks which are prone to overpressuring as soon as burial begins again (Heller et al, 2015 andEmery, 2016). A typical (shale) pressure profile when applying the principles of "primary" and "secondary" disequilibrium compaction in wells within the study area, can be described as shown in the diagram below ( Figure 4) and is also illustrated in the Pressure-Depth plot in Figure 3.…”
Section: Geological Pressure Model For the Browse Basin And The Southmentioning
confidence: 99%
“…However, this relatively simple model, describing porosity/effective stress evolution due to "primary" disequilibrium compaction, fails to capture the shale pressure in most of the study wells. For the purpose of this study, this relatively simplistic model can be further split into "primary" and "secondary" disequilibrium compaction where primary disequilibrium compaction relates to overpressure generated in rocks for the first time, whereas secondary disequilibrium compaction applies to rocks where overpressure has been previously generated, but, due to depositional hiatus or unconformity, the overpressure has dissipated, leading to low porosity/permeability rocks which are prone to overpressuring as soon as burial begins again (Heller et al, 2015 andEmery, 2016). A typical (shale) pressure profile when applying the principles of "primary" and "secondary" disequilibrium compaction in wells within the study area, can be described as shown in the diagram below ( Figure 4) and is also illustrated in the Pressure-Depth plot in Figure 3.…”
Section: Geological Pressure Model For the Browse Basin And The Southmentioning
confidence: 99%